Heritability of quantitative autism spectrum traits in adults: A family‐based study. Issue 8 (10th July 2021) - Taylor, Sara C.; Steeman, Samantha; Gehringer, Brielle N.; Dow, Holly C.; Langer, Allison; Rawot, Eric; Perez, Leat; Goodman, Matthew; Smernoff, Zoe; Grewal, Mahip; Eshraghi, Oceania; Pallathra, Ashley A.; et al.
Abstract: Autism spectrum disorder (ASD) comprises a multi‐dimensional set of quantitative behavioral traits expressed along a continuum in autistic and neurotypical individuals. ASD diagnosis—a dichotomous trait—is known to be highly heritable and has been used as the phenotype for most ASD genetic studies. But less is known about the heritability of autism spectrum quantitative traits, especially in adults, an important prerequisite for gene discovery. We sought to measure the heritability of many autism‐relevant quantitative traits in adults high in autism spectrum traits and their extended family members. Among adults high in autism spectrum traits ( n  = 158) and their extended family members ( n  = 245), we calculated univariate and bivariate heritability estimates for 19 autism spectrum traits across several behavioral domains. We found nearly all tested autism spectrum quantitative traits to be significantly heritable ( h 2  = 0.24–0.79), including overall ASD traits, restricted repetitive behaviors, broader autism phenotype traits, social anxiety, and executive functioning. The degree of shared heritability varied based on method and specificity of the assessment measure. We found high shared heritability for the self‐report measures and for most of the informant‐report measures, with little shared heritability among performance‐based cognition tasks. These findings suggest that many autism spectrum quantitative traits would be good, feasible candidates for future genetics studies, allowing for an increase in the power of autism gene discovery. Our findings suggest that the degree of shared heritability between traits depends on the assessment method (self‐report vs. informant‐report vs. performance‐based tasks), as well as trait‐specificity. Lay Summary: We found that the scores from questionnaires and tasks measuring different types of behaviors and abilities related to autism spectrum disorder (ASD) were heritable (strongly influenced by gene variants passed down through a family) among autistic adults and their family members. These findings mean that these scores can be used in future studies interested in identifying specific genes and gene variants that are associated with different behaviors and abilities related with ASD.